Cancer herbal cures for mobile application - Mohamad, Siti Sarah; Raja Mamat, Raja Nazirah; Norzu, Siti Aishah (University Community Transformation Centre, Universiti Putra Malaysia, 2017)
The purpose of Cancer Herbals Cures application is to those who are looking for simple, natural or herbal cures for cancer diseases with minimal effects. Herbal Cures application offer herbal that use to treat cancer disease. In this application we only provide cures for lung cancer, breast cancer and colorectal cancer. These cancers are among top of cancer at Malaysia. These applications provide type of herbal, information about the herbal, how to use and the contact information. Other than that, user can give feedback and give rating on this application for improvement of our application.